Події 1914-1922 років в Україні: їх сенс та історичне значення (Частина 4) - Semenko, Vitalii (Chernivtsi National University, 2020)
The editorial board continues to publish the most important documents that characterize the state and progress of the Ukrainian national liberation movement, the attitude of other states towards this movement in the early twentieth century. The publication of the selected documents from the first three volumes of the collection of documents “Events in Ukraine 1914-1922 their Importance and Historical Background” was carried out in the 39th, 40th and 41th volumes of the Collection. Currently we are publishing our research from the fourth volume. The compilers selected 27 documents or fragments, which chronologically cover the period from October 19, 1918 to November 14, 1922. They represent the vision of the Ukrainian problem of that time by the ruling circles of Austria and Germany, reflect the final stage of Pavlo Skoropadskyʼs activity at the head of the Ukrainian State. Most of them reveal the historical background and efforts of the Directory, prominent figures of Ukrainian Peopleʼs Republic and Western Region of the Ukrainian Peopleʼs Republic in the development and preservation of Ukraine, establishing relations with the victorious states and neighbors, resistance to aggressors. Published documents shed light on the following issues: the military, political, and economic situation in Ukraine before and during the Directoryʼs uprising against Hetman P. Skoropadsky (999, 1019, 1021, 1029, 1030); preconditions and formation of the Western Ukrainian Peopleʼs Republic, difficulties of its existence at the initial stage (1003, 1004, 1005); preconditions and principles of unification of the Ukrainian States (1011, 1013); protest of Ukrainian politicians against the decision of the Paris Conference on the occupation of part of the Ukrainian lands by Poland (1015); position and first foreign policy steps of the Directory (1033); unification of the Ukrainian Peopleʼs Republic and the Western Ukrainian Peopleʼs Republic, their representations abroad (1049, 1050, 1059); problems of the Directoryʼs relations with the Entente and the Ukrainоphobic regime of A. Denikin, the war with the Soviet-Russian troops in 1919-1920 (1060, 1061, 1064, 1067, 1068); international political recognition of the Ukrainian Peopleʼs Republic and the possibility of restoring Ukrainian statehood in 1920-1921 (1072, 1073, 1082, 1086, 1995); the political situation in Ukraine in 1922 (1109, 1115). We hope that these documents will be insightful and informative for both students and experts of international relations and the history of Ukraine in the early twentieth century. Having selected the documents from different parts of the book, we preserved their serial and page numbers, the style of the titles and captions. We also present a list of abbreviations in the original.
Events in Ukraine 1914–1922 Their Importance and Historical Background (Part IV)
Keywords: Austria, Hetman, Directory, The Western Ukrainian Peopleʼs Republic, Germany, Ukraine, Ukrainian national movement, The Ukrainian Peopleʼs Republic.